Propuesta para mejorar el desempeño del subproceso de compras de las empresas de Grupo de Llano - Motato Torres, Mónica Rocio (Universidad Antonio Nariño, 2023)
In this research the causes that affect the performance of the purchasing sub-process in the companies of Grupo de Llano were addressed, taking into account the general performance of all the collaborators in their indicators, their opinions about it and the information collected by the leaders of the process, the research was developed starting from an initial diagnosis in which the information obtained was analyzed and in this way the strategies that would minimize the findings were defined and that as a result of this analysis leads to the main objective which is the development of the proposal for improvement. For the progress of the investigation a methodology with mixed approach was used due to its qualitative scope based on the particularities received by the personnel from their functions and their feelings; and at the same time quantitative supported in historical data and numerical performance; allowing in this way to know the origin or root cause of the subprocess performance. As a conclusion to the exercise, an improvement proposal was made focused on the development of suppliers from the purchasing management taking into account the commercial interaction of supplier-buyer, to reach this result it was determined that the major cause of these negative results is due to the lack of business alliances with local suppliers in the region and to develop a growth process with those that would allow the continuity of the process in its normal cycle. Keywords: Findings, strategies, supplier, buyer, alliances.